Energetic considerations for engineering novel biochemistries in photosynthetic organisms - Strand, Deserah D.; Walker, Berkley J. (Frontiers in Plant Science, 2023)
Humans have been harnessing biology to make valuable compounds for generations. From beer and biofuels to pharmaceuticals, biology provides an efficient alternative to industrial processes. With the continuing advancement of molecular tools to genetically modify organisms, biotechnology is poised to solve urgent global problems related to environment, increasing population, and public health. However, the light dependent reactions of photosynthesis are constrained to produce a fixed stoichiometry of ATP and reducing equivalents that may not match the newly introduced synthetic metabolism, leading to inefficiency or damage. While photosynthetic organisms have evolved several ways to modify the ATP/NADPH output from their thylakoid electron transport chain, it is unknown if the native energy balancing mechanisms grant enough flexibility to match the demands of the synthetic metabolism. In this review we discuss the role of photosynthesis in the biotech industry, and the energetic considerations of using photosynthesis to power synthetic biology.